Bioinformatics analyses of the proteome of Holothuria tubulosa coelomic fluid and the first evidence of primary cilium in coelomocyte cells - La Paglia, Laura; Mauro, Manuela; Arizza, Vincenzo; Urso, Alfonso; Simon, Sugár; Drahos, Laszlo; di Stefano, Vita; Luparello, Claudio; Vazzana, Mirella; Vizzini, Aiti (Frontiers in Immunology, 2025)
The holothurian immune system is characterized by complex defense mechanisms that act through humoral and cellular pathways. Coelomocites are the cellular component of coelomic fluid, and they are involved in host defense, stress response, wound healing, organ regeneration, and tissue homeostasis. The close phylogenetic relationship between Holothuria tubulosa and chordate phylum makes it a good model for studying the evolution of immune processes. To elucidate the immune landscape in H. tubulosa, we applied an approach combining proteomic analysis of coelomic fluid separated into cellular fraction and extracellular fraction and bioinformatics and in silico analyses. A Search Tool for the Retrieval of Interacting Genes/Protein analysis indicated a highly functional homology to the human protein of immune recognition factors, non-canonical immune-related proteins, signaling molecules, and effector protein, cytoskeleton, and actin remodeling, and provided the first evidence in invertebrate immune cells of an intracellular protein fraction linked to ancestral structure resembling primary cilium involved in cell signaling.